Rekontekstualisasi Pemikiran Seyyed Hossein Nasr tentang Bangunan Ilmu Pengetahuan dan Pendidikan Islam - Asfa Widiyanto (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article discusses the conception of science and its significance for the reconstruction of Islamic educat-ion, by analyzing and contextualizing the thoughts of Seyyed Hossein Nasr. Nasr is considered a figure who has compe-tence in history of science and philosophy with special emphasis on Islamic science and philosophy. In the earlier phase of his life, he acquainted himself with the thoughts of prominent thinkers both from East and West, and with the very issue of the encounter between East and West. This position makes the thoughts of Nasr on science having their distinctive character. The first part of this paper investigates the construct and characteristics of Islamic science as well as the hierarchy and the idea of unity in Islamic science. The second part of this paper is dealing with the reformulation of philosophical basis of Islamic education, most specifically in the domain of ontology, epistemology and axiology. The third is dealing with the attempts of reconstructing the system of Islamic education, most notably pertaining to the aim of education, educator, student, means of education, and milieu of education.